Relationship Conflict : Conflict in Parent-Child, Friendship and Romantic Relationships. - Canary, Dan J. (Sage series on close relationships., 1995)
Conflict is a natural and inevitable aspect of most close personal relationships - the crucial issue is not whether it exists, but the way it is managed. Skilfully portraying both developmental or healthy conflict, and destructive or unhealthy conflict, this interdisciplinary volume leads to a better understanding of this vital aspect of relationships. Integrating current research and theory, the authors explore the variation in definitions of interpersonal conflict; review popular survey and observational measures; and discuss specific concerns regarding parent-child relationships, con.